Federalism in the Northern Territory : statehood and aboriginal political development - Gibbins, Roger, 1947-; Australian National University. North Australia Research Unit. (Darwin, Australia : Australian National University, North Australia Research Unit, 1988)
Impact of statehood on Aboriginal interests, aspirations; government policy, economic development; Aboriginal Land Rights (Northern Territory) Act 1976; mining; tourism and National Parks; electoral participation; political party policies; local/community government; land councils.
Includes bibliographical references (p. 140-148).
Keywords: Aboriginal Australians -- Northern Territory -- Government relations; Federal government -- Northern Territory; Aboriginal Australians -- Suffrage -- Northern Territory; Land rights - Excisions and leases - Land grants and leases to Aborigines; Economic sectors - Tourism; Law - Land - State and Territory - Northern Territory; Law - Constitutional law; Land rights - Mining industry; Government policy - Integration; Land rights - Excisions - Land grants and leases to Aborigines; Land rights - Conservation areas; Politics and Government - Elections; Law - Land - Commonwealth; Councils - Land Councils; Politics and Government - Local government; Politics and Government - Political parties - Liberal Party / National Party; Land rights - Excisions and leases - Mining leases; Northern Territory -- Politics and government; Northern Territory (NT)